Pengaruh financial technology terhadap kinerja profitabilitas perusahaan otomotif yang terdaftar di Bursa Efek Indonesia periode 2021-2023 - Putri Astri Babaubun; Lintje Kalangi; Steven J. Tangkuman (Riset Akuntansi dan Manajemen Pragmatis, 2026)
This study aims to examine the effect of Financial Technology (FinTech) adoption on the profitability of automotive companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. FinTech adoption is measured using the FinTech Adoption Index (FAI) derived from annual reports and official publications, while profitability is proxied by Return on Assets (ROA). This research employs a quantitative approach with purposive sampling, resulting in 11 companies and 33 observations. Data are analyzed using simple linear regression with IBM SPSS 26. The results indicate that FinTech has a positive and significant effect on profitability, with a regression coefficient of 0.060 and a significance value of 0.023 (p < 0.05). This finding suggests that higher FinTech adoption enhances firms’ efficiency in utilizing assets, thereby improving profitability. However, the coefficient of determination (R²) of 0.156 implies that FinTech explains only 15.6% of the variation in profitability, indicating the presence of other influencing factors. These findings support Signaling Theory and Agency Theory, highlighting that FinTech adoption serves as a positive signal to stakeholders while reducing information asymmetry and agency costs. This study contributes to the limited literature on FinTech in the automotive sector and provides practical implications for firms in optimizing digital transformation strategies to enhance financial performance.